Popular, Commercial or Didactic? Some Notes on Fasihi Pendwa. Issue 1 (15th June 2016) - Gromov, Mikhail
Abstract : The purpose of this article is to outline a number of specific traits intrinsic to a literary phenomenon that is known as fasihi pendwa (relative Kiswahili equivalent of the term "popular literature"). The article uses as research material popular writing in Kiswahili from Tanzania, since Kenyan popular literature in the language still appears to be in its formation phase. Using two basic genres of fasihi pendwa – that is, love story and detective story – the article outlines their common traits which characterize these genres on different levels. The author stresses the fact that in Tanzania fasihi pendwa performs mainly educating and moralizing functions, serving as vehicles for local moral norms, social demands and worldviews.